2018
DOI: 10.2967/jnumed.118.210161
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Metabolically Active Tumor Volume and Total Lesion Glycolysis as 18F-FDG PET/CT–derived Prognostic Biomarkers in Chemorefractory Metastatic Colorectal Cancer

Abstract: This study aimed to validate the prognostic value of baseline whole-body metabolic active tumor volume (WB-MATV) and total lesion glycolysis (WB-TLG) measured with [F]fluorodeoxyglucose positron emission tomography-computed tomography (F-FDG PET/CT) in a large cohort of chemorefractory metastatic colorectal cancer (mCRC) patients treated with multikinase inhibitors (MKI). The secondary objective of this study was to compare WB-MATV and WB-TLG respective prognostic values to commonly used clinical prognostic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
(32 reference statements)
2
28
1
Order By: Relevance
“…16,30 In contrast, all metabolic parameters, including SUV max and SUV peak , with the exception of MTV, were significantly increased in the patients who rapidly relapsed as compared with the patients with prolonged RFS, suggesting that metabolic characteristics could potentially predict the benefit of surgery in individual cases. In contrast with other reports, MTV did not appear as a strong predictive factor, 25,31 even if a tendency toward a higher MTV was observed in ER patients. This could be related to the limited size of the groups but also to the fact that the prognostic impact of tumor burden Accordingly, this study evaluates intrinsic tumor behavior, independent of the response to chemotherapy, as the prognostic value of the response to chemotherapy may vary in patients with CRLM, depending on the number of cycles and on the method used for assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…16,30 In contrast, all metabolic parameters, including SUV max and SUV peak , with the exception of MTV, were significantly increased in the patients who rapidly relapsed as compared with the patients with prolonged RFS, suggesting that metabolic characteristics could potentially predict the benefit of surgery in individual cases. In contrast with other reports, MTV did not appear as a strong predictive factor, 25,31 even if a tendency toward a higher MTV was observed in ER patients. This could be related to the limited size of the groups but also to the fact that the prognostic impact of tumor burden Accordingly, this study evaluates intrinsic tumor behavior, independent of the response to chemotherapy, as the prognostic value of the response to chemotherapy may vary in patients with CRLM, depending on the number of cycles and on the method used for assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study of patients with chemorefractory metastatic colorectal cancer found that those with a high metabolically active tumour volume, as measured via fluorodeoxyglucose (FDG)‐PET–CT, had a significantly shorter OS. Although that study was similar to the present one, the analysis included extrahepatic metastases and detected only FDG‐PET‐positive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Contal and O'Quigley's method (26) was used to determine the optimal cfDNA cutoff for survival prediction. The optimal cutoff for WB-MATV was determined to be 100 cm 3 , as previously reported (16). The SUV max , SUV mean , and SUV peak PET parameters were considered as continuous variables for survival prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body 18 F-FDG PET/CT allows the assessment of both tumor burden and its glycolytic activity (14,15). Baseline wholebody metabolically active tumor volume (WB-MATV), representing the patient's active tumor load before treatment, was recently validated by our group as a strong prognostic imaging biomarker in a large cohort of chemorefractory mCRC patients (16). Interestingly, another PET parameter evaluating the glycolytic activity of the disease, SUV max , was recently reported to be correlated with cfDNA in advanced non-small cell lung cancer patients (17).…”
mentioning
confidence: 99%